Evaluation of antimicrobial activity and identification of yellow pigmented marine sponge-associated fungi from Teluk Awur, Jepara, Central Java - Mada Triandala Sibero; Desy Wulan Triningsih; Ocky Karna Radjasa; Agus Sabdono; Agus Trianto (Indonesian Journal of Biotechnology, 2016)
Marine sponge associated fungi are known as potential source of metabolites with various biological activities. Natural pigment is one of metabolite which produced by microorgisms. Several researches reported the antimicrobial activity from natural pigment. Unfortunatelly there are lack of information about marine fungi natural pigment and its producer. The aims of this research were to identify yellow pigmented Indonesian marine sponge-associated fungi, to extract the pigment, and to study the antimicrobial activity of the pigment against clinical MDR bacteria and clinical pathogenic fungi. Sponge associated-fungus isolate MT23 was successfully identified as Trichoderma parareesei. The fungal pigment could be extracted only in methanol with yield 6,22±0,29%. The pigment could inhibitted S. typhi and E. coli MDR strains. The biggest antibacterial activity was shown by concentration 1000µg/mL against S. typhi with inhibition zone was 4.03±0.06 mm.